Antibacterial and Antifungal Activities of Ethiopian Medicinal Plants: A Systematic Review - Nigussie, Dereje; Davey, Gail; Tufa, Takele Beyene; Brewster, Malcolm; Legesse, Belete Adefris; Fekadu, Abebaw; Makonnen, Eyasu (Frontiers in Pharmacology, 2021)
Background: Bacterial and fungal infections are a significant public health problem worldwide. In Ethiopia, this includes acute lymphangioadenitis in lymphoedema sufferers. Plant-based traditional medicines are used to treat infections in many countries and are culturally established in Ethiopia. Ethiopian medicinal plants found to have antibacterial and antifungal activities were reviewed with the aim of increasing information about the treatment of wound infections in patients with lymphoedema. Methods: This study collates data from published articles on medicinal plants with antibacterial and antifungal activities in Ethiopia. A systematic search of Scopus, EMBASE, PUBMED/MEDLINE, and Google Scholar was undertaken. The Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) guidelines were followed. The protocol was registered on PROSPERO with registration number CRD42019127471. All controlled studies of in vitro antibacterial and antifungal activities were considered. All articles containing the descriptors published until June 28, 2019, were included. The outcome was measured as percent inhibition of microbial growth. For quality assessment of the individual in vitro studies, OECD guidelines, and the WHO-Good Laboratory Practice (GLP) handbook were used. Results: Seventy-nine studies met the inclusion criteria. A total of 150 plant species and 3 compounds had been tested against 42 species of bacteria, while 43 plant species had been tested against 22 species of fungus. Conclusions: Ethiopian medicinal plants are shown to have promising activity against bacteria and fungi. Azadiractha indica and Lawsonia inerms are the plant materials most studied against a wide range of gram-negative and positive bacteria, and fungal species.